2014
DOI: 10.1038/mt.2013.142
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Vaccine for Respiratory Syncytial Virus Provides Protection Without Disease Potentiation

Abstract: Respiratory syncytial virus (RSV) is a major cause of infectious lower respiratory disease in infants and the elderly. As there is no vaccine for RSV, we developed a genetic vaccine approach that induced protection of the entire respiratory tract from a single parenteral administration. The approach was based on adenovirus vectors derived from newly isolated nonhuman primate viruses with low seroprevalence. We show for the first time that a single intramuscular (IM) injection of the replication-deficient adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 44 publications
1
39
1
Order By: Relevance
“…We chose a dose of 2x10 5 PFU that was recently reported to be sufficient to assess the efficacy of RSV vaccines (Garg et al, 2014; Johnson et al, 2014; Kim et al, 2014; Murata and Catherman, 2012; Nguyen et al, 2012; Schmidt et al, 2012). We also found that the PBS or PR8 WT group of mice that were infected with 2x10 5 PFU RSV showed a high titer of approximately up to 10 4 PFU from lungs at day 5 post infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We chose a dose of 2x10 5 PFU that was recently reported to be sufficient to assess the efficacy of RSV vaccines (Garg et al, 2014; Johnson et al, 2014; Kim et al, 2014; Murata and Catherman, 2012; Nguyen et al, 2012; Schmidt et al, 2012). We also found that the PBS or PR8 WT group of mice that were infected with 2x10 5 PFU RSV showed a high titer of approximately up to 10 4 PFU from lungs at day 5 post infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, delivery of adenoviral vectors by small aerosols to the lungs of rhesus macaques resulted in potent immune responses even in animals with preexisting adenoviral vector immunity (31,35,51), suggesting that such vector immunity can be overcome by mucosal delivery of adenoviral vectors. In addition, several adenovirus vectors have been developed based on chimpanzee or gorilla adenoviruses, which combine efficacy with evasion of preexisting vector specific neutralizing antibody responses (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the development of vaccines within this category that either improve immunogenicity despite greater vaccine virus attenuation [37,38], improve manufacturing capacity [39], or improve stability of surface proteins and immunogenicity [38,40,41] will provide potential solutions for immunizing the antigen-naïve infant. Other approaches that deliver vaccine antigens through gene-based vectors [4244] or nucleic acid [45,46] are another possible avenue towards the goal of infant immunization. These approaches induce a pattern of immune responses analogous to live virus and have not been associated with enhanced pathology in animal models of RSV infection, and so are likely to be safe in antigen-naïve infants.…”
Section: Vaccine Approaches To Protect Infantsmentioning
confidence: 99%